Wastewater engineering : (McGraw-Hill, 2014)
Volume 1 -- 1. Introduction to Wastewater Treatment and Process Analysis -- 2. Wastewater Characteristics -- 3. Wastewater Flowrates and Constituent Loadings -- 4. Wastewater Treatment Process Selection, Design, and Implementation -- 5. Physical Unit Operations -- 6. Chemical Unit Processes -- 7. Fundamentals of Biological Treatment -- 8. Suspended Growth Biological Treatment Processes -- 9. Attached Growth and Combined Biological Treatment Processes -- Volume 2 -- 10. Anaerobic Suspended and Attached Growth Biological Treatment Processes -- 11. Separation Processes for Removal of Residual Constituents -- 12. Disinfection Processes -- 13. Processing and Treatment of Sludges -- 14. Biosolids Processing, Resource Recovery and Beneficial Use -- 15. Plant Recycle Flow Treatment and Nutrient Recovery -- 16. Air Emissions from Wastewater Treatment Facilities and Their Control -- 17. Energy Considerations in Wastewater Management -- 18. Wastewater Management: Future Challenges and Opportunties.